History of factional divisions in political parties in Thai democracy - Sok Chueak, Nakhon (Thai Social Science Journal, 2025)
Separation of factions within Thai political parties at present, It has evolved from internal divisions in the history of politics and government since the past. Before the change of government in 1932, although at present there are divisions within political parties in Thailand’s democracy, through a new form of government through the constitution and law and the format of the new election format. Instead, it caused more and more divisions within the party and coupled with a weak political party structure make party system Politics still has divisions. Especially, the rise to power of the military authoritarian party in 2007, the party that changed the constitution. Restoring the autonomy of various groups, destroying the strength of political parties, for the result of entering state power. The results of the latest Thai election appeared. The importance of the group was made more important. Because the leaders of the Thai military government and the allies wanted to make changes in order to weaken the pro-Thaksin party, but in the end the Palang Pracharat Party established by the military government also faced the greatest problem of division and revert to the original natural state of being an uncertain group in a political party